Transmisi Gelombang pada Pemecah Gelombang Ambang Rendah Ganda - Surendro, Bambang; Yuwono, Nur; Darsono, Suseno (MEDIA KOMUNIKASI TEKNIK SIPIL, 2014)
Coastal protection efforts can be done in various ways, among others, by making alow threshold breakwaters (sumerged breakwater). Every building in addition there is certainly no shortage of excess. With several weaknesses breakwater low threshold, then conducted research with the title “Wave Transmission At Low Threshold Dual-breaking waves". The study was conducted in the Hydraulic laboratory of the Faculty of Engineering, Tidar Magelang University, with variations of the model as follows: Model I : single low threshold breakwater piles of stones (PGARTTB) with peak width (B)=120 cm Model II : a low threshold double breakwater piles of stones (PGARGTB) formed by reducing material PGARTTB protective stone that is in the middle as much as 8.89%, 20%, 33.33%, and 46.67%. The results showed that: a) Reduction of material protection on the stone breakwater lowthreshold single pile of stones (PGARTTB) affect the magnitude of the wave transmission, b) reduced protective stone will increase the value of the wave transmission coefficient c) for each reduction of 1% a protective stone, waves of up 0.2788% transmission, d) the increase in transmission waves are caused by the reduced friction between the base and peak wave breakwaters low threshold.